2021
DOI: 10.3389/fmicb.2021.690270
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an Integrated mCherry Red Fluorescent Protein Expression System for Labeling and Tracing in Lactiplantibacillus plantarum WCFS1

Abstract: Thorough intestinal adhesion and colonization greatly promote the probiotic properties of lactic acid bacteria (LAB). Labeling and tracing with fluorescent proteins are effective and reliable for studying the in vivo physiological activities of LAB including localization, adhesion, and colonization. Lactiplantibacillus plantarum WCFS1 was successfully traced with a red fluorescent protein (RFP), which was expressed by the bacteria-carrying recombinant plasmids. In this study, we aimed to construct a stable RFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Lys26 and 34 were also mutated to Gln26 and Asp34 to inhibit trypsin digestion (Figure 1a) [54]. Promoter spacers for mGLP-1 expression were optimized as described before [55,56]. Signal peptides Lp_0600 and Lp_0373 were added in front of the modified glp-1 gene for secretion, and arginine, the functional site of trypsin, was used as the dividing point.…”
Section: Construction and Expression Of W-0373-mglp-1mentioning
confidence: 99%
“…Lys26 and 34 were also mutated to Gln26 and Asp34 to inhibit trypsin digestion (Figure 1a) [54]. Promoter spacers for mGLP-1 expression were optimized as described before [55,56]. Signal peptides Lp_0600 and Lp_0373 were added in front of the modified glp-1 gene for secretion, and arginine, the functional site of trypsin, was used as the dividing point.…”
Section: Construction and Expression Of W-0373-mglp-1mentioning
confidence: 99%
“…But the fungus seemed to colonize the rhizoplane abundantly, where it formed viable conidiophores [16,17]. Currently, labeling and tracing with fluorescent proteins are effective and reliable for studying the in vivo physiological activities of the fungal localization, adhesion and colonization [22]. Green fluorescent protein (GFP) was also successfully expressed in P. chlamydosporia [23].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to bioluminescence, direct visualization of recombinant LAB vector expressing fluorescent reporter protein produces intense signals under shorter exposure times, making it a more convenient and less time-consuming scheme for tracking with high spatial and temporal resolution. However, most previous studies indicated that probiotic persistence during gastrointestinal transit is strain-specific/dose-dependent and primarily relies on the intrinsic efficiency of the bacterial expression system. …”
Section: Introductionmentioning
confidence: 99%